Evolutionary divergence in the pan-Atlantic mangrove Avicennia germinans - (:unkn) unknown (My University, 2000)
Cuticular hydrocarbon composition was determined for 18 populations of Avicennia germinans (Avicenniaceae) collected from West Africa, Florida, the Pacific coast of Mexico and French Guyana. Variation in covariance structure among the hydrocarbons was evaluated from correlations among the traits for each of the populations and from a hierarchical common principal components analysis. Principal components ordinations of populations based on the 171 z* transformed correlation coefficients, onto which a minimal spanning tree was superimposed, suggested a network in which French Guyanan populations formed a nexus from which African populations differentiated biochemically from Floridan and Mexican groups. Common principal components analysis provided further support for the differentiation in covariance structure among these biochemical traits of African populations. Pacific coast Mexican populations appeared to have diverged less in covariation among traits from Atlantic American sources than did the northern (Floridan) and southern (French Guyanan) Atlantic American populations from one another. The complete isolation of Pacific coast sources after emergence of the Central American isthmus during the Pliocene provides a reference for comparison of levels of differentiation among regions that suggests an underlying pattern of divergence in this species. Partial Mantel matrix tests revealed significant geographic effects, with no significant climatic effects. Our results provide support for recognition of a major differentiation between Old and New World sources within the taxon and indicate the need for a full revision of this species.
Keywords: African Research